Discourse Processes Adopts the Transparency and Openness Promotion Guidelines. Issue 2 (7th February 2023) - Kaakinen, Johanna K.; Bohn-Gettler, Catherine M.
ABSTRACT: The Discourse Processes editorial team has decided to adopt the Transparency and Openness Promotion guidelines. The purpose of the guidelines is to help researchers, journal editors, and reviewers adopt practices that support transparency, openness, and reproducibility of research. The guidelines include eight transparency standards regarding (1) citations of data and materials, (2) data sharing, (3) analytic methods, (4) research materials, (5) design and analysis methods, (6) preregistration of the study, (7) preregistration of the analysis plan, and (8) replication studies. We describe each standard, how they are implemented, and what it means from the perspective of an author who wishes to publish their work in Discourse Processes .